Extrusion and injection-molding of glass fiber/MAPP/polypropylene: Effect of coupling agent on DSC, DMA, and mechanical properties - Hassan, A.; Rahman, N.A.; Yahya, R. (2011)
Glass fiber-reinforced PP composites compatibilized with maleic anhydride grafted polypropylene (MAPP) were compounded with a twin-screw extruder and injection molded. The composite specimens were subjected to DSC, DMA, tensile, and flexural property characterizations. DSC results showed that the presence of glass fiber loading and MAPP produced insignificant effect on the melting temperature of the composites. The melting enthalpy was decreased with glass fiber loadings, but no significant change was noted in the crystalline peak temperatures (Tc). Incorporation of the compatibilizer led to a reduction in Tc. Incorporation of glass fiber reduced the crystalline enthalpy of compatibilized and uncompatibilized systems. DMA results showed that composite properties were affected by the presence of the compatibilizer at low fiber loading (â¤14 Vf). Tensile and flexural properties also showed sensible improvement of compatibilized against uncompatibilized composite systems.